The Islamic Law Perspective Of Precautionary Principle On Transboundary Movement Of Living Modified Organisms (LMOS) - Wartini, Sri (UI Scholars Hub, 2016)
The aim of the research is to examine the Islamic law perspective of precautionary principle on transboundary movement of living modified organisms (hereinafter LMOs) based on maslahah mursalah (public interest) and sadd al-dhara’i (blocking the means). The international trade of LMOs may affect the human health and environment in the importing states. Most of the importing states are Muslim states. Thus, it is important to examine the transboundary movement of LMOs from the Islamic law perspective. In order to elaborate on the issue, the reseach addresses the following questions: First, how is the relationship between man and nature (khalīfahand nature)? Second, what are the basic Islamic principles relevant to transboundary movement of LMOs based on justice and equality. Finally, it examines comprehensively what are the justification of implementing Precautionary Principle based on maslahah mursalah and sadd al-dhara’i on transboundary movement of LMOs. The research finds that the precautionary principle is justiviable based on based on maslahah mursalah and sadd al-dhara’i on transboundary movement of LMOs